Flow-Dependent Transport of Glyphosate, Dioxins, and Lead in an Urban River: A Scenario-Based HEC-RAS Numerical Study of Sungai Perai, Malaysia - Parthartlee, Jolibon; Puay, How Tion (International Journal on Engineering Technology and Infrastructure Development, 2026)
Municipal waste effluent introduces persistent and toxic contaminants into urban river systems, with their transport and environmental impact strongly influenced by hydrological conditions. This study investigates the flow-dependent transport behavior of three distinct municipal-related pollutants which is glyphosate (first-order decay rate k = 0.023 day-1), dioxins (k = 0.231 day-1) and lead (Pb, k = 0.005 day-1) in the Sungai Perai catchment using numerical modelling. A one-dimensional steady-flow hydraulic model coupled with the General Constituent Simulation Module (GCSM) in HEC-RAS was developed to simulate pollutant transport under three representative flow scenarios: high flow (50 m3/s), baseflow (36 m3/s), and low flow (20 m3/s). Seven effluent-affected locations along the river were modelled using a triangular concentration profile over a 2.5-hour discharge period. Due to the lack of local gauge height data for calibration, the model is applied as an exploratory scenario tool. The results demonstrate that river flow conditions exert a dominant control on pollutant dilution, downstream propagation, and persistence. Low-flow conditions represented the highest water quality risk, yielding peak simulated concentrations that limited the river's inherent dilution capacity. Persistent constituents such as Dioxins and Lead exhibited prolonged downstream residence compared to more weakly reactive constituents, exhibited prolonged downstream residence times compared to highly decaying inputs. Across all scenarios, a consistent pollutant accumulation zone was observed within a mid-reach hotspot between CH4400 and CH4800, driven by local hydraulic channel characteristics. These findings highlight the importance of incorporating flow sensitivity into effluent impact assessments and demonstrate the value of scenario-based modelling for supporting pollution risk evaluation and river basin management in urban catchments.